COHESIVE TIES IN PROMOTIONAL TEXTS: A MULTIMODAL TRANSLATION PERSPECTIVE ON FILM POSTERS - Svetlana Yu. Pavlina; Marina R. Safina; Olga D. Prasolova (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2025)
This study considers multimodal texts of film posters in the light of functional pragmatics and intersemiosis. Film posters lie at the intersection of cinematic and advertising discourses, they cross national boundaries promoting films globally. It informs about our investigation of these promotional texts in the light of multimodal translation. Our research is set in the integrative framework encompassing Social Semiotics and Multimodal Translation. The material includes multimodal texts of film posters in English and their counterparts localized for the Russian audience. The sample texts are analyzed at the levels of meaning-building and reception. We examine cohesive linkages between different semiotic modes in the original posters, then we reveal if these ties are preserved or broken in the course of multimodal translation. Finally, we analyze how the translated versions are perceived by the Russian-speaking viewers. To this end, we conduct an experiment in the form of an interview. The findings reveal that the semantic ties uniting verbal and pictorial elements are not always rendered accurately in the course of multimodal translation, which tends to be assessed negatively by the recipients. However, some participants of the experiment positively evaluate localized posters with broken cohesive links finding them intriguing. It goes in line with the main pragmatic functions of advertising texts as they should not only inform but also stimulate interest in the film, intrigue being a powerful tool to do it. Our empirical study establishes correlation between the genre characteristics of a multimodal text and the perception of its intersemiotic ties.